Microplastics: Impacts on Environment and Human Health Hazards - Meshram , Leena N.; Mhatre, Kirti J. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Plastic waste is not biodegraded and can only be broken down, predominantly by physical processes, into small particles of micron to nanometre size. Microplastic pollution is becoming a major issue for human health due to the recent discovery of microplastics (MP) in most ecosystems. Microplastic have been found to have significant negative impacts on both human health and the environment. Plastic particles less than 150 μm can be ingested by living organisms, migrate through the intestinal wall and reach lymph nodes and other body organs. There are increasing concerns over the environmental and human health impacts associated to exposure to these pollutants. The long-term and irreversible risks to ecosystems and human health indicate for mitigation measures to be taken to halt the accumulation of plastics and microplastics in the environment. The surfaces of plastic fragments can be carrying disease-causing organisms andacts as a vector for diseases. The microplastics found in water and soil carry different types of contaminants and serve as carriers for bacteria and persistent organic pollutants. MP and nanoplastics may pose acute and chronic toxicity, carcinogenicity, developmental toxicity, and genotoxicity. This study conducts a review with primary objectives of MP, including their definition, ecological impacts with respect to direct and indirect effects; effects on aquatic biota, marine ecosystem, fresh water ecosystem, animal health and seafood, human health hazards; control measures; and knowledge gaps.